2017
DOI: 10.26656/fr.2017.5.104
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant and antifungal properties of Mentha x piperita L. (peppermint) and Mentha arvensis L. (cornmint) samples

Abstract: Essential oils and infusions from commercial peppermint sachets (CPS), and noncommercial genuine peppermint (NCP) and cornmint (NCC) samples were analyzed by GC/MS and LC/MS. Minimum inhibitory concentration (MIC) of mint oils against Fusarium moniliforme, Aspergillus niger and Aspergillus fumigates was determined. Antioxidant potential was monitored by total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and soybean oil oxidation tests. CPS and NCC oils had lower menthofuran content than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…In the micro‐dilution method, MIC values of 2.50 and 1.00 (mg/ml) respectively. Similarly, anti‐fungal application of oils or extracts results were shown in the previous literature representing high sensitivity of M. × piperita against many of fungal strains Sacchromyces cerevisiae (Sandasi et al, ; Tyagi & Malik, ) Candida albicans ( Pramila et al, ; Tyagi & Malik, ; Zaidi & Dahiya, ) , Fusarium oxysporum (Desam et al, ; Tyagi & Malik, ) , Mucor spp (Tyagi & Malik, ), Aspergillus niger (Hussain et al, ; Mahboubi & Kazempour, ; Nilo et al, ; Tyagi & Malik, ), Aspergillus flavus (Hussain et al, ; Tyagi & Malik, ) and Penicillium digitatum (Tyagi & Malik, ). Anti‐fungal activity is depicted in Table .…”
Section: Pharmacological Activities Of M × Piperitamentioning
confidence: 54%
See 2 more Smart Citations
“…In the micro‐dilution method, MIC values of 2.50 and 1.00 (mg/ml) respectively. Similarly, anti‐fungal application of oils or extracts results were shown in the previous literature representing high sensitivity of M. × piperita against many of fungal strains Sacchromyces cerevisiae (Sandasi et al, ; Tyagi & Malik, ) Candida albicans ( Pramila et al, ; Tyagi & Malik, ; Zaidi & Dahiya, ) , Fusarium oxysporum (Desam et al, ; Tyagi & Malik, ) , Mucor spp (Tyagi & Malik, ), Aspergillus niger (Hussain et al, ; Mahboubi & Kazempour, ; Nilo et al, ; Tyagi & Malik, ), Aspergillus flavus (Hussain et al, ; Tyagi & Malik, ) and Penicillium digitatum (Tyagi & Malik, ). Anti‐fungal activity is depicted in Table .…”
Section: Pharmacological Activities Of M × Piperitamentioning
confidence: 54%
“…Flavones (luteolin, luteolin O ‐diglucuronide, luteolin O ‐glucuronide, luteolin 7‐ O ‐ β ‐glucuronide, luteolin 7‐ O ‐rutinoside and isorhoifolin), flavanones (eriodictyol, naringin, eriodictyol‐glycopyranosyl rhamno pyranoside, naringenin7‐ O ‐ β ‐glucoside, hesperidin and eriocitrin), methoxyflavones (gardenin B, 5,6‐dihydroxy‐7,8,3,4‐tetra methoxy flavone and salvigenin) and flavonols (catechin, rutin, [−]‐epicatechin, quercetin, quercetin‐4‐glucoside, kaempferol 7‐ O ‐rutinoside and myricetin O ‐glucoside) isolated and identified from M . × peperita (Fecka & Turek, ; Hoffmann & Lunder, ; Kapp et al, ; Krzyzanowska et al, ; Nilo et al, ; Voirin et al, ). The phyto‐constituents of these flavonoids are shown in Figure .…”
Section: Therapeutically Active Phytochemical Constituents Present Inmentioning
confidence: 99%
See 1 more Smart Citation
“…found almost 11 to 12 types of fungus (including Candida albicans, Trichophyton mentagrophytes, Aspergillus fumigatus etc.) against which peppermint oil has shown significant inhibitory activity [23] According to Nilo et al (2017) the extract of peppermint leaves has fungicidal effect against the aggrandizement of some fungus including Fusarium moniliforme, Aspergillus niger and Aspergillus fumigatus [24] . According to Hussain et al (2010), peppermint oil was found to show an inhibitory effect on Aspergillus niger, Aspergillus flavus, Rhizopus solani and Fusarium solani [25] .…”
Section: Anti-bacterial Actionmentioning
confidence: 99%
“…and thyme ( Thymus sp.). The isomeric (+)-neomenthol is found in Japanese peppermint oil, while (−)-neoisomenthol makes up to one percent in geranium oil [ 3 , 4 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%